2009
DOI: 10.1093/cercor/bhp002
|View full text |Cite
|
Sign up to set email alerts
|

Attention Reshapes Center-Surround Receptive Field Structure in Macaque Cortical Area MT

Abstract: Directing spatial attention to a location inside the classical receptive field (cRF) of a neuron in macaque medial temporal area (MT) shifts the center of the cRF toward the attended location. Here we investigate the influence of spatial attention on the profile of the inhibitory surround present in many MT neurons. Two monkeys attended to the fixation point or to 1 of 2 random dot patterns (RDPs) placed inside or next to the cRF, whereas a third RDP (the probe) was briefly presented in quick succession across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
116
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(131 citation statements)
references
References 56 publications
12
116
3
Order By: Relevance
“…This confirmed previous results obtained by Connor and colleagues [11]. Additionally, Anton-Erxleben et al [12] showed that directing attention within the RF of a given neuron will shrink this neuron's RF (in addition to shifting it), but directing it just outside the RF will instead extend the RF towards the focus of attention. David et al [13] showed that attention can shift receptive fields not only spatially, but also feature-wise: the neuron's RF is altered to be more responsive to the type of feature Simple modulations of neural responses cannot readily explain this effect: increasing or decreasing a neuron's response may push its entire response curve up or down, but cannot by itself shift it laterally, much less restructure it over fine feature space.…”
Section: A Attention Has Complex Effects On Neural Responsessupporting
confidence: 91%
See 1 more Smart Citation
“…This confirmed previous results obtained by Connor and colleagues [11]. Additionally, Anton-Erxleben et al [12] showed that directing attention within the RF of a given neuron will shrink this neuron's RF (in addition to shifting it), but directing it just outside the RF will instead extend the RF towards the focus of attention. David et al [13] showed that attention can shift receptive fields not only spatially, but also feature-wise: the neuron's RF is altered to be more responsive to the type of feature Simple modulations of neural responses cannot readily explain this effect: increasing or decreasing a neuron's response may push its entire response curve up or down, but cannot by itself shift it laterally, much less restructure it over fine feature space.…”
Section: A Attention Has Complex Effects On Neural Responsessupporting
confidence: 91%
“…However, their model assumes a fixed "Mexican Hat" connectivity pattern in which short-range connections are excitatory while long-range connections are inhibitory, while in reality the sign of lateral interactions actually varies with stimulus intensity (a same stimulus in the surround will increase response to a weak central stimulus, but decrease response to a strong central stimulus [18]). Perhaps more importantly, the model of Compte and Wang does not readily explain how attention can extend a neuron's RF of nearby neurons when it is located just outside this RF rather than inside it, as reported by Anton-Erxleben et al [12].…”
Section: A Attention Has Complex Effects On Neural Responsesmentioning
confidence: 91%
“…This hypothesis is consistent with neurophysiological studies on endogenous attention, demonstrating that a neuron's response to its preferred stimulus is greatly reduced when the preferred stimulus is not attended, and an attended, non-preferred stimulus is also presented within the neuron's receptive field. These findings suggest that attention contracts the cell's receptive field around the attended stimulus (e.g., Anton-Erxleben et al, 2009;Moran and Desimone, 1985;Reynolds and Desimone, 1999;Womelsdorf et al, 2006).…”
mentioning
confidence: 88%
“…One possibility is that during attentive tracking of a moving object, the profile of a visual neuron's RF undergoes dynamic changes similar to those reported during tasks where attention is directed to stationary objects (Connor et al, 1996;Womelsdorf et al, 2006;Anton-Erxleben et al, 2009). For example, it is possible that during attentive tracking, a neuron multiplicatively increases the response to a passing tracked stimulus over the entire RF excitatory area, producing a homogenous expansion of the RF.…”
Section: Introductionmentioning
confidence: 94%